The Expression of Mentality and National Character in The Proverbs of English and Uzbek People - Atoyeva Shahnoza Alidotovna (Genius Publishing Group, 2022)
Each nation has its own way of life and cultural characteristics in the development of national traits and unique traditions. It is known from life experience that the cultural beliefs and awareness of a nation are highly dependent on what they have witnessed throughout history. Folklore is the most important aspect that allows people to get acquainted with the way of life and traditions of other peoples, well-known facts about their daily life. Brief and morally evaluated genres of folklore are proverbs and expressions.
Keywords: Proverb; metaphor; cognitive linguistics; family